Rhetorical and artistic styles in narrative text of Ahlam Mostaganemi and Louise Erdrich - Hleel, Alaa Sadiq (2020)
This study contends that the study of classical Arabic rhetoric has been limited to Arabic literary texts such as poetry and prose. This had led to the interest of contemporary rhetorical studies to include novels which are also considered a form of creative literary texts. This research aims to compare the novels of Ahlam Mostaghanemi and Louise Erdrich using classical Arabic rhetoric and artistic methods. It also aims to identify and analyse their rhetoric, and the eloquence of the narrative (based on the internal and external elements of the stylistic approach employed). The researcher first employed the descriptive analytical approach to identify and extract rhetorical elements and artistic methods in their works, and subsequently used the comparative approach to identify the similarities and differences between them. This study is significant in that it presents a new experience in comparative studies of rhetorical methods between two novelists representing two different languages. The rhetorical methods that are found similar are questioning, metaphor, element of elegance and ingenuity in the expression. However, in terms of differences, there are variations in the amount of questions as well as the element of elegance. It is discovered that there are more questions in Ahlam Mostaghanemi’s novels than there are in Louise Erdrich’s novels. In terms of the eloquence of the texts, three methods were found. They are partial rhetorical methods, and the narrative eloquence and image, all of which were successfully employed by both the novelists in their novels. While Ahlam Mostaghanemi used rhetoric to depict the artistic side, Louise Erdrich was more inclined to use rhetoric to depict the basic idea of the novel. She also excelled in using fictional terminologies or occult terms that are associated with the local culture of the Ojibo tribes.